O condicional evidencial no gênero jornalístico - Lourenço, Fabiana Pirotta Camargo (Universidade Federal de São Carlos, 2016)
In this research, we propose the study of a type of evidential marker not yet described in Brazilian Portuguese (BP), the conditional tense, which indicates how the speaker had access to the information conveyed in the statement, in other words, what is the source of the information. The “evidential conditional value” has been studied in several languages. In French, Dendale (2010) seeks to characterize it and considers it as an essentially evidential use. In European Portuguese (EP), Oliveira (2013) analyzes it as a way that allows speakers to establish a detachment from the propositional content of their statements. On the other hand, Squartini (2001) describes this use in Romance languages (European Portuguese, English, French, Spanish and Italian), considering it a grammatical phenomenon internal to the verbal system. Therefore, based on the functionalist theory, in this research it is intended to make a detailed description of this conditional use in real contexts of use in BP. Based on occurrences provided by a corpus of the journalistic domain, comprising editorials, news and opinion articles, we aim to describe the functioning of the “conditional evidential value”, looking to set the syntactic, semantic and pragmatic characteristics of this use. With this characterization will be possible to verify if the conditional morpheme can be considered a way of grammatically marking evidentiality in BP, a process which happens in other languages. This description will enable, besides, the verification of the discursive function of this use in the journalistic genres that compose the corpus. It is expected that the results of this research provide a refinement of the evidentiality category in BP, providing, in addition, a contribution to those who work with the journalistic genre, since this use can be considered an important discursive strategy in this area.
Keywords: Evidencialidade; Condicional; Gênero jornalístico; Funcionalismo; Evidentiality; Conditional; Journalistic genre; Functionalism; LINGUISTICA, LETRAS E ARTES::LINGUISTICA